Memperkuat Karakter Islami Mahasiswi Melalui Integritas Kurikulum: Analasisi Perspektif Wan Mohd Nor Wan Daud - Siti Mutia Kanzha Shibby; Tatu Azizatu Zahra; Trya Nanda Karima (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2025)
The abstract is written in English, containing elements of the purpose of writing, methods, results, and conclusion. Written between 200-250 characters with the formation of one paragraph that includes all of these elements. (Palatino Linotype 11, Justify) This study aims to analyze efforts to strengthen the Islamic character of female students through curriculum integrity using Wan Mohd Nor Wan Daud's perspective. This approach emphasizes the importance of integrating science and Islamic values ​​in the higher education system, especially in shaping student character. Through literature review and conceptual analysis, this study explores how Wan Mohd Nor Wan Daud's views can be applied in curriculum development that focuses on the formation of solid Islamic morals. The results of the study indicate that the implementation of curriculum integrity that is in line with Islamic values ​​is able to support the development of a more holistic female student character, both in terms of spiritual, moral, and intellectual aspects. These findings provide an important contribution to curriculum development in higher education, especially in the context of Islamic education.